Optimal analysis of battery energy storage for reduction of power fluctuation from PV system in Mae Hong Son province - Borirat Jintanasombat (2018)
© 2015 IEEE. The problems of the power fluctuation always occur with renewable sources of wind and solar energy that can cause many problems in grid system. A solution of these problems is using energy storage for reduction of power fluctuation. Mae Sariang, Mae Hong Son province, Thailand is an urban forestry area. This area has a PV power plant 2 MW connected to grid system without the battery energy storage system (BESS) and no regulations on ramp rate limit of distributed generation. In order to solve these problems, distribution utility and a PV power plant owner has cooperated to plan to install BESS. Therefore, this paper studies analysis and comparison 4 different technology of the BESS such as advanced Lead Acid battery (adv.LA), Lithium ion battery (Li-ion), Sodium Nickel Chloride battery (NaNiCl) and Sodium Sulfur battery (NaS) that is appropriated for installing in this system. The optimization problem is formulated to maximize the revenue gained from providing energy into grid system from operation of BESS with PV system on each ramp rate limit by using The General Algebraic Modeling System (GAMS) and solved by using CPLEX solver. From simulation results, when BESS has installed, the fluctuation of power output before fed to grid system is reduced significantly. In addition, the highest revenue gained and payback period less than 4 years can get from installing NaNiCl battery with PV system in this area.